Simultaneous Genotyping of Four Single Nucleotide Polymorphisms Associated with Risk Factors of Hemostasis Disorders - E. Bashmakova, Eugenia; V. Krasitskaya, Vasilisa; A. Frank, Ludmila (Combinatorial Chemistry & High Throughput Screening, 2015)
Multiplex simultaneous genotyping technique was developed for four polymorphisms in genes coding for blood coagulation factors and homocysteine metabolism which are considered as thrombophilia related mutations: FV Leiden, FII G20210A, MTHFR C677T, and FVII G10976A. It is based on primer extension reaction with the following bioluminescent solid-phase microassay. At that, two different in bioluminescence obelin mutants were applied to simultaneous detection of two gene allelic variants. The assay is carried out in microtiter plate format and provides fast and reliable genotyping of four single nucleotide polymorphisms in four different genes within 2.5 hours. A large number of clinical samples were analyzed and the obtained results were found to be in complete correlation with those obtained by using conventional RT-PCR techniques.
Keywords: multiplex PCR